Effects of Different Irrigation Management and Nitrogen Rate on Sorghum (Sorghum bicolor L.) Growth, Yield and Soil Nitrogen Accumulation with Drip Irrigation - Zelin Wang; Tangzhe Nie; Dehao Lu; Peng Zhang; Jianfeng Li; Fanghao Li; Zhongxue Zhang; Peng Chen; Lili Jiang; Changlei Dai; Peter M. Waller (Agronomy, 2024)
Sorghum (Sorghum bicolor L.) has emerged as a pivotal global food crop. Consequently, it is imperative to explore sustainable and eco-friendly strategies to achieve sustainable sorghum production with a high yield. This study aimed to reveal the effects of irrigation management and nitrogen rates and their interactions on sorghum growth traits, yield and soil nitrate-N and ammonium-N accumulation to improve irrigation and nitrogen practices under drip irrigation. A 2-year (2021 and 2022) field experiment was conducted on drip-irrigated fertilized sorghum in Heilongjiang Province to investigate the effects of three lower levels of soil moisture (80% (HI), 70% (NI), and 60% (LI) of field capacity) with four nitrogen rates at 225, 150, 75 and 0 kg/ha (designated as HN, NN, LN and WN, respectively) on sorghum growth, yield and soil nitrogen accumulation. The results indicated that irrigation management and nitrogen rate interaction had a significant effect on sorghum growth (plant height, stem diameter, leaf area index (LAI), and SPAD value), yield, aboveground biomass and 0~60 cm soil nitrogen accumulation (p < 0.05). The NNHI treatment demonstrated the highest plant height (120.9 and 121.8 cm) and LAI (2.738 and 2.645) in 2021 and 2022, and there was a significant positive correlation between plant height, LAI, and yield (p < 0.01). However, the NNNI treatment exhibited the highest yield (7477.41 and 7362.27 kg/ha) in 2021 and 2022, sorghum yield increased and then decreased with an increase in irrigation management and nitrogen rate. In addition, soil nitrate-N and ammonium-N accumulation were significantly affected by the interaction of irrigation management and nitrogen rate (p < 0.05) while irrigation management had no significant effect on the accumulation of nitrate-N and ammonium-N. Soil nitrate-N and ammonium-N accumulation increased with the increasing nitrogen rate. Although yield differences between the NNNI and HNNI treatments were not significant, the NNNI treatment with a lower soil moisture limit of 70% field capacity and a nitrogen rate of 150 kg/ha accumulated 10.4% less nitrate-N in soil than the HNNI treatment, reduced risk of nitrate nitrogen leaching. The regression analysis indicated that the optimal irrigation management and nitrogen rate management practices of 71.93% of the soil moisture lower limit and 144.58 kg/ha of nitrogen rate was an optimal strategy for favorable sorghum growth, high-yielding and low soil nitrate-N accumulation of sorghum. This study provides a scientific reference for precise water and fertilizer management in sorghum.